Customer Review on Confidence, Readiness and Security in Electronic Commerce (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays, the world of technologies is evolving. We used to do business within big companies and now, there is e-commerce. The revolution of e-commerce is only just getting started. Over the next few years, e-Commerce is predicted to be widely accessible. E-commerce would have a significant effect on the formation of a truly mass-market phenomenon. It will also have a profound impact on the way trade is done by each person and company. In addition, e-commerce is responsible for implementing digital interactive TV that will bring further e-commerce beyond the realms of PC literacy. The fact that e-commerce is a future way of business really change the landscape of business. The proliferation of e-commerce companies saw the rise of the worldwide number of online companies. Consumers are now opted for business online, which in contrast to conventional transactions is dramatically convenient. E-commerce firms have, in any case, more advantages compared to conventional brick and mortal companies, but the difficulties and problems facing e-commerce businesses cannot be missed. This study illustrated the difficulties and problems of e-commerce and a range of solutions. Trust, readiness and protection are among the problems. Proposed solutions are proposed for each of the problems and challenges. Alibaba Group for example also face this common challenges. Alibaba Group being chosen in this case study as Alibaba was exceptionally skilled in establishing credibility. Despite its revealed vulnerability in intellectual property rights, Alibaba keep on continued give efforts to create credibility and will help to facilitate the evolution of e-commerce platform. Such attempts have made Alibaba is a standard model for e-business but overall, the challenges in this study are collected among all e-commerce platform, not only Alibaba Group.